2020
DOI: 10.1080/1331677x.2019.1702076
|View full text |Cite
|
Sign up to set email alerts
|

Does virtual currency development harm financial stocks’ value? Comparing Taiwan and China markets

Abstract: This research incorporated virtual currency development factors into the capital asset pricing model (CAPM) and interpreted the effects of bitcoin and fin-tech on the capital market through a deduction of the portfolio theory and innovation diffusion theory (IDT) on changes to financial stocks' value. This paper examined a total of 67,166 panel data of financial stocks in the two emerging markets of Taiwan and China between July 2016 and April 2019, presenting the following significant findings. (1) Financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The neo-industrial marathon will involve two poles, on the one hand, the U.S. and other developed countries, and on the other, Russia, China, India, and perhaps other developing countries, which will determine the trends of global economic development this century. A new class of assets called cryptocurrencies adds to global uncertainty (Ho, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The neo-industrial marathon will involve two poles, on the one hand, the U.S. and other developed countries, and on the other, Russia, China, India, and perhaps other developing countries, which will determine the trends of global economic development this century. A new class of assets called cryptocurrencies adds to global uncertainty (Ho, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding these advantages, VCs also have some inherent disadvantages which, among others, include the complete change in transaction or investment models once payments are executed and the decline in revenues of major players in the financial sector such as insurers’ service charges and banks’ traditional spread models. Stated differently, the development of VCs may result in significant changes in the financial sector (Huang, 2021; Ho, 2020; Yeoh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have reported on the significant influence exerted by VCs on stock performance (Shahzad et al , 2020; Stensås et al , 2019; Bouri et al , 2017), these studies did not distinguish whether the sample countries covered actually recognize the legitimacy of VC transactions or not, with the exception of Ho (2020) who investigates the influence of VC development on financial stocks’ value in Taiwan and China. The author finds that VCs, in particular Bitcoins, exert more significant impact on the value of financial stocks in Taiwan, which does not recognize the legitimacy of Bitcoin, as compared to China.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations